Training on Processing Liquid Organic Fertilizer (POC) from Rice Washing Waste, Brown Sugar and EM4 in Siontapina Village: Pelatihan Pengolahan Pupuk Organik Cair (Poc) dari Limbah Cucian Beras, Gula Merah Dan Em4 di Desa Siontapina - Irwan Irwan; Kamarudin Kamarudin; Tarno Tarno; Manan Manan; Suarti Suarti; Puji Fitria Zainal; Iskandar Salju (Room of Civil Society Development, 2026)
This community service activity aimed to provide practical knowledge and hands-on experience to housewives and farmer group members in Siontapina Village in converting rice-washing water into liquid organic fertilizer (LOF). The activity was conducted on October 14, 2025, with 10 participants through socialization and direct demonstration. The formulation consisted of 600 mL of rice-washing water, one tablespoon of brown sugar (approximately 10 g), and 50 mL of EM4, followed by seven days of fermentation. Observation showed a cloudy yellow liquid with a distinctive fermented aroma resembling tape, a small amount of white foam, and gas pressure inside the container. The LOF was introduced for use after dilution at a 1:10 ratio. The activity demonstrates the potential of a simple household-resource-based technology, although chemical quality and effectiveness on plant growth were not examined.